Science and religion - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
Are science and religion completely at odds as many believe? This is a common assumption in modern culture, but upon further investigation we find that certain fundamental scientific beliefs actually evolved out of religious thought. Upon deeper analysis, the two disciplines may not be as separate and distinct as is commonly thought. In this edition of Matter and Beyond we'll hear the perspectives of thought leaders who, along with a growing number of scholars, are inviting us to re-think some of our basic assumptions about science and religion.
Executive producer, Nasuhi yurt.
Host : MaryLynn Schiavi.
DVD format
Keywords: Religion and science